Review of Submarine Landslides in the Eastern Indonesia Region - Hananto Kurnio; Tommy Naibaho; Catur Purwanto (BULLETIN OF THE MARINE GEOLOGY, 2019)
his paper reviews submarine landslide potential in the eastern Indonesia by analyzing published and recently acquired bathymetric data and interpreting seismic reflection data. This review aims to study and invent hazards that might affect seafloor infrastructure construction such as optic cables, especially in the eastern Indonesia Region. The hazards were also recognized as source of tsunamis such as Palu Bay 2018 and Babi Island north of Flores Island in 1992. On the other hand, submarine landslide is a common process of basin fill sedimentation in the region. As blessed with many active volcanoes, it has 130 of total the world 400, Indonesia should aware of tsunami induced by volcanoes especially the ones closed to the sea. There are five active volcanoes frequently produce tsunami in historical times: Anak Krakatau, Sunda Strait; Makian, Maluku Province; Sangihe, Sulawesi; Teon and Nila, Banda Sea; and Iliwerung, Lembata Island, east Lesser Sunda Islands.Key words: submarine landslide, volcanic tsunami, seafloor infrastructure, eastern Indonesia Makalah ini menelaah potensi langsoran dasar laut di wilayah Timur Indonesia melalui analisis publikasi dan data batimetri yang baru diambil serta penafsiran data seismic refleksi. Tinjauan longsoran dasar laut dimaksudkan untuk mempelajari dan menginventarisasi bencana yang mungkin bisa mempengaruhi pembangunan infrastruktur dasar laut seperti halnya kabel optic, terutama di wilayah Timur Indonesia. Bencana tersebut telah dikenal sebagai sumber beberapa tsunami seperti Teluk Palu 2018 dan Pulau Babi utara Lombok di tahun 1992. Sebaliknya, longsoran dasar laut merupakan proses sedimentasi pengisian cekungan yang biasa terjadi di wilayah tersebut. Dikarunia akan gunungapi terbanyak di dunia, sebab memiliki 130 dari 400 dunia, Indonesia harus menyadari bahaya tsunami yang ditimbulkan oleh aktivitas gunungapi terutama yang dekat laut. Terdapat lima gunungapi aktif yang sering menghasilkan tsunami dalam sejarah: Anak Krakatau, Selat Sunda; Makian, Provinsi Maluku; Sangihe, Sulawesi; Teon dan Nila, Laut Banda; dan Iliwerung, Pulau Lembata, Nusa Tenggara Timur.Kata kunci: longsoran dasar laut, tsunami gunungapi, infrastruktur dasar laut, Wilayah Indonesia Timur